Benchmarks for food safety curriculum in the East African Community - Kang'ethe, Erastus K.; Mutua, Florence K.; Hung Nguyen-Viet (International Livestock Research Institute, 2022)
The International Livestock Research Institute, the Food and Agriculture Organization of the United Nations and the Inter-University Council of East Africa have been working with food safety experts from universities in the East African Community (EAC) to develop benchmarks for a Bachelor of Science program in food safety, aimed at enhancing food safety in the EAC region. A workshop to finalize the process was held on 22–24 March 2022 in Kampala, Uganda.